Fiscal multipliers in advanced and developing countries: Evidence from military spending - Viacheslav Sheremirov; Sandra Spirovska (Federal Reserve Bank of Boston, 2019)
Using novel data on military spending for 129 countries in the period 1988-2013, this paper provides new evidence on the effects of government spending on output in advanced and developing countries. Identifying government-spending shocks with an exogenous variation in military spending, we estimate one-year fiscal multipliers in the range 0.75-0.85. The cumulative multipliers remain significantly different from zero within three years after the shock. We find substantial heterogeneity in the multipliers across groups of countries. We then explore three potential sources leading to heterogeneous effects of fiscal policy: the state of the economy, openness to trade, and the exchange-rate regime. We find that the multipliers are especially large in recessions, in closed economies, and under a fixed exchange rate. We also discuss other potential reasons for heterogeneous effects of fiscal policy, such as its implementation and coordination with the monetary authority.
Keywords: E32; E62; F44; H56; O23; 330; fiscal policy; military spending; multiplier